(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Since the turn of the century, vocabulary teaching has become an integral part of language teaching, which was once undervalued, because in any language, vocabulary is basic to all the four language skills. And conventional teaching methods included having students memorize a list of words either with their translations into L1 or definitions, drills and language chunks unlike contemporary methods which emphasize the effectiveness of applying modern technologies. The main purpose of this paper is to prove that games are an effective tool in terms of second language vocabulary acquisition. This paper, to a large extent, deals with a review of researches on teaching vocabulary through games. In addition, potential challenges are also included.